LAYANAN KONSELING BEHAVIORAL DENGAN TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN TANGGUNG JAWAB BELAJAR SISWA SMP N 1 JEPARA - Zahro, Fadya Noviana; Masturi, Masturi; Gudnanto, Gudnanto (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The objectives of this study are: (1) Describe the factors that cause the level of learning responsibility of students of SMP N 1 Jepara. (2) To obtain an increase in student learning responsibility through behavioral counseling services with self-management techniques at SMP N 1 Jepara.This type of research is qualitative research in the form of a case study carried out at SMP N 1 Jepara. The subjects in this study were 2 students, namely FNZ and VHS who experienced low learning responsibility problems and took counseling for three meetings. The data collection methods used are observation, interview, and documentation methods.The results of this study that the process of providing behavioral counseling services with self-management techniques, counselors are able to change their problematic behavior into behaviors that counselors hope that students can actively enter class, students can pay attention to teachers when teaching, students can be responsible for completing assignments, students collect assignments on time, and obey school rules.